Desvelando a autoavaliação institucional da Universidade Federal da Paraíba (UFPB) a partir da visão dos gestores - Ribeiro, Wagner Leite (2023)
This thesis is linked to studies related to the Evaluation of Higher Education in Brazil, a problem correlated to the line of research on Educational Policies, of the Graduate Program in Education (PPGE), at the Federal University of Paraíba (UFPB). The research focused on Institutional Self-Assessment, considering the National Higher Education Assessment System (SINAES) - Law no. 10,861, of April 14, 2004, and with the objective of analyzing the role of institutional self-assessment and its repercussions on the decision-making process of the UFPB, from the perspective of the managers of the Own Assessment Committee (CPA) in order to enable the process quality improvement. Therefore, the theoretical and conceptual basis used included the conceptions of the Evaluating and Regulating State, the Educational Policies and, more specifically, the SINAES. Thus, the UFPB institutional self-assessment experiences, developed in the last 5 (five) years, more specifically in the period from 2017 to 2021, were analyzed in order to understand their senses, meanings in a view of the institution in its entirety. In order to reach the general objective of this investigation, we sought to know the trajectories, dismemberments and advances of the UFPB in terms of Institutional Evaluation, based on the results evidenced in the Internal Institutional Evaluation Reports (RAAIs), prepared by the Own Evaluation Committee (CPA) and, therefore, the case study was chosen as the method of procedure. As a strategy to develop the empirical study, interviews were conducted with CPA managers in order to identify the strengths, weaknesses, opportunities and threats within the institution, considering the use of the SWOT Matrix as a tool for analysis and interpretation of data. In view of this, the results of the research revealed that institutional self-assessment policies are provided for in the Institutional Development Plan (PDI) (2019 - 2023) of the UFPB, however, it was identified that the axes and indicators defined by the External Institutional Assessment Instrument ( AIIE) were not fully included in the analyzed RAAIs. Furthermore, there was a lack of a specific computational system for collecting and processing self-assessment data at the UFPB, in order to reach a larger number of respondents, speed up the process and elaborate subsidies for the improvement of its institutional efficiency and academic effectiveness. and social. It was also verified the need for improvements in the conditions of physical infrastructure, updating of the CPA Internal Regulations - in force since 2004, adjustments regarding the parity of the segments that make up the commission, as well as the consolidation of a culture of self-assessment at the institution, in accordance with SINAES precepts.